2021
DOI: 10.2196/26600
|View full text |Cite
|
Sign up to set email alerts
|

Support Seeking in the Postpartum Period: Content Analysis of Posts in Web-Based Parenting Discussion Groups

Abstract: Background The transition from pregnancy to motherhood is a major developmental phase that can be challenging for both women and their families. For new mothers, the postpartum period is recognized as a critical period for increased risk of both physical and mental health concerns. For this reason, it is imperative that women receive accurate, evidence-based information during this time. Objective This study aims to explore the conversations of new moth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Additionally, knowledge of infant care has been found to play a significant role in building women's sense of maternal competency, particularly for firsttime mothers (37). Typically, new mothers engage in web-based forums to seek help and support during the postpartum period, and web-based communities play an important role in maternal peer social support, information seeking, and early parenting practices (38).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, knowledge of infant care has been found to play a significant role in building women's sense of maternal competency, particularly for firsttime mothers (37). Typically, new mothers engage in web-based forums to seek help and support during the postpartum period, and web-based communities play an important role in maternal peer social support, information seeking, and early parenting practices (38).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, text frequency search was able to reveal the most dominant topics of concern, while word frequency calculations traced all stemmed words (minimum three letters) and automatic sentiment analysis revealed the emotional indicators through the use of predefined scores for emotionally-charged words. Meanwhile, a slightly altered grounded theory analysis, implementing the six-face approach by Braun and Clarke ( 4 ) was chosen as most appropriate to deal with the unknown area of parenting forums ( 5 , 6 ). Results showed that new mothers frequently seek help through such forums and are highly influenced by them, while the most usual topics of concern deal with infant health and well-being.…”
Section: Resultsmentioning
confidence: 99%
“…Each search term combination was entered individually in the search engine. For websites, the first 2 pages of results for each search term were screened for inclusion, similar to previous studies [ 19 , 24 , 25 ]. For apps, searches were entered into the Google Play and Apple App Store databases without any specified search categories.…”
Section: Methodsmentioning
confidence: 99%